The impact of Paclitaxel-based hyperthermic intraperitoneal chemotherapy in advanced high-grade serous ovarian cancer patients - interim analysis of safety and immediate efficacy of a randomized control trial (C-HOC trial) - Qun Wang; Hua Liu; Yuhong Shen; Lifei Shen; Jian Li; Weiwei Feng (BMC, 2024)
Abstract Objective This study evaluates the potential superiority of combining paclitaxel-based hyperthermic intraperitoneal chemotherapy (HIPEC) with sequential intravenous neoadjuvant chemotherapy over intravenous neoadjuvant chemotherapy alone in Chinese patients with Federation of Gynecology and Obstetrics (FIGO) stage IIIC, IVA and IVB high-grade serous ovarian/fallopian tube carcinoma (HGSOC). This interim analysis focuses on the safety and immediate efficacy of both regimens to determine the feasibility of the planned trial (C-HOC Trial). Methods In a single-center, open-label, randomized control trial, FIGO stage IIIC, IVA, and IVB HGSOC patients (FAGOTTI score ≥ 8 during laparoscopic exploration) unsuitable for optimal cytoreduction in primary debulking surgery (PDS) were randomized 2:1 during laparoscopic exploration. The Experiment Group (HIPEC Group) received one cycle of intraperitoneal neoadjuvant laparoscopic hyperthermic intraperitoneal chemotherapy (paclitaxel) followed by three cycles of intravenous chemotherapy (paclitaxel plus carboplatin), while the Control Group received only three cycles of intravenous chemotherapy. Both groups subsequently underwent interval debulking surgery (IDS). The adverse effects of chemotherapy, postoperative complications, and pathological chemotherapy response scores (CRS) after IDS were compared. Results Among 65 enrolled patients, 39 HIPEC Group and 21 Control Group patients underwent IDS. Grade 3-4 chemotherapy-related adverse effects were primarily hematological with no significant differences between the two groups. The HIPEC Group exhibited a higher proportion of CRS 3 (20.5% vs. 4.8%; P = 0.000). R0 resection rates in IDS were 69.2% (HIPEC Group) and 66.7% (Control Group). R2 resection occurred in 2.6% (HIPEC Group) and 14.3% (Control Group) cases. No reoperations or postoperative deaths were reported, and complications were managed conservatively. Conclusions Combining HIPEC with IV NACT in treating ovarian cancer demonstrated safety and feasibility, with no increased chemotherapy-related adverse effects or postoperative complications. HIPEC improved tumor response to neoadjuvant chemotherapy, potentially enhancing progression-free survival (PFS). However, the final overall survival results are pending, determining if HIPEC combined with IV NACT is superior to IV NACT alone.